Plasma Neutrophil Gelatinase-associated Lipocalin and Leukocyte Differential Count in Children with Febrile Urinary Tract Infection - Min Hwa Son; Hyung Eun Yim; Kee Hwan Yoo (Korean Society of Pediatric Nephrology, 2021)
Purpose We aimed to study the association of plasma neutrophil gelatinase-associated lipocalin (pNGAL) and leukocyte differential count in children with febrile urinary tract infection (UTI). Methods Medical records of 154 children aged 1 month to 13 years with febrile UTI who were hospitalized were retrospectively reviewed. Associations between pNGAL levels and blood leukocyte differential count at admission and after 48 hours of treatment were investigated in children with or without acute pyelonephritis (APN). Results The APN group (n=82) showed higher pNGAL levels, neutrophil count, monocyte count, and neutrophil-to-lymphocyte ratio (NLR), compared to the non-APN group (n=72) (all P<0.05). After adjustment for age and sex, pNGAL showed positive correlations with neutrophil count and NLR in both groups (all P<0.05). Additionally, it was correlated with the monocyte-to-lymphocyte ratio (MLR) only in the APN group (P<0.05). Before and after treatment, pNGAL was positively correlated with neutrophil count, NLR, and MLR in patients with APN while it was related with neutrophil count and NLR in those without APN (all P<0.05). Areas under the receiver operating curve of pNGAL, neutrophil count, NLR, and MLR for predicting APN were 0.804, 0.760, 0.730, and 0.636, respectively (all P<0.05). Only pNGAL was independently associated with the presence of APN in a multivariable logistic regression analysis (P<0.05). Conclusion In children with febrile UTIs, pNGAL might be associated with leukocyte differential count and the presence of APN.